Constructing Co3O4 Nanowire@NiCo2O4 Nanosheet Hierarchical Array as Electrode Material for High-Performance Supercapacitor - Bo Xu; Lu Pan; Yaqi Wang; Menglong Liu (Nanomaterials)
The Co3O4 nanowire@NiCo2O4 nanosheet hierarchical array was constructed on Ni foam using hydrothermal and annealing approaches in turn, from which a NiCo2O4 nanosheet could self-assemble on the Co3O4 nanowire. The structure and morphology of the Co3O4 nanowire@NiCo2O4 nanosheet hierarchical array were characterized via XRD, EDS, SEM, and FESEM, respectively. The electrochemical performance of the composite array was measured via a cyclic voltammetry curve, galvanostatic current charge–discharge, charge–discharge cycle, and electrochemical impedance and then compared with the Co3O4 nanowire. The results show that the Co3O4 nanowire@NiCo2O4 nanosheet hierarchical array could reach a high value of 2034 F g−1 at a current density of 2.5 A g−1. After 5000 galvanostatic charge–discharge cycles, the specific capacitance of the Co3O4 nanowire@NiCo2O4 nanosheet hierarchical array could still maintain 94.7% of the original value. Therefore, the Co3O4 nanowire@NiCo2O4 nanosheet hierarchical array would be a desirable electrode material for a high-performance supercapacitor.